2020
DOI: 10.3390/molecules25204851
|View full text |Cite
|
Sign up to set email alerts
|

Morusin Suppresses Cancer Cell Invasion and MMP-2 Expression through ERK Signaling in Human Nasopharyngeal Carcinoma

Abstract: The most important cause of treatment failure of nasopharyngeal carcinoma (NPC) patients is metastasis, including regional lymph nodes or distant metastasis, resulting in a poor prognosis and challenges for treatment. In the present study, we investigated the in vitro anti- tumoral properties of morusin on human nasopharyngeal carcinoma HONE-1, NPC-39, and NPC-BM cells. Our study revealed that morusin suppressed the migration and invasion abilities of the three NPC cells. Gelatin zymography assay and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(49 reference statements)
0
6
1
Order By: Relevance
“…[11] Additionally, it has substantial antitumor potential by regulating JNK, ERK, STAT3, and NFκB. [20][21][22] Because of the complexity of morusin, several investigations are needed to confirm the mechanism of therapeutic activity. Thus, we used bioinformatics which can streamline complicated processes to research the anticancer effect of morusin, forecast potential mechanisms and serve as the foundation and guide for subsequent in vitro or in vivo tests.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Additionally, it has substantial antitumor potential by regulating JNK, ERK, STAT3, and NFκB. [20][21][22] Because of the complexity of morusin, several investigations are needed to confirm the mechanism of therapeutic activity. Thus, we used bioinformatics which can streamline complicated processes to research the anticancer effect of morusin, forecast potential mechanisms and serve as the foundation and guide for subsequent in vitro or in vivo tests.…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinases were reportedly associated with NPC cell invasion and migration, [19][20][21][22][23] and could regulate the functions of MMPs. 24,25 To determine whether DHM can affect the expressions of MAPKs, Western blotting assay was performed.…”
Section: Effects Of Dihydromyricetin On the Mitogenactivated Protein ...mentioning
confidence: 99%
“…According to a recent study, morusin can prevent human NPC HONE-1, NPC-39, and NPC-BM cells from migrating and invading. These findings showed that morusin is effective at preventing NPC invasion and metastasis ( Huang et al, 2020 ). In addition to being a tumor marker in NPC, MMP-2 is also linked to lymph node metastases and a poor prognosis ( Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 96%
“…MMP-2 is well known for degrading ECM as well as being a tumor marker for head and neck cancer with a bad prognosis. According to studies, morusin blocks the ability of cancer cells to migrate and invade by preventing the expression of the MMP-2 protein ( Huang et al, 2020 ). Previous research has shown that early MMP activity inhibition can be used to prevent cancer metastasis, and morusin may be a promising cancer therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%